Debt Policy Analysis Through Profitability as Moderating Variables in Property & Real Estate Companies That Go Public on the IDX - Wijayanti, Erni; Pertiwi, Tri Kartika (Nusantara Science and Technology Proceedings, 2020)
This study is aimed at examining profitability in moderating the effect of dividend policy and business risk on debt policy by using the population of property & real estate companies that go public on the IDX for the 2016-2018 period. Using purposive sampling to obtain a sample of 34 companies. Using moderated regression analysis with absolute difference testing as an analysis technique. So that the dividend policy results are obtained, business risk can contribute to debt policy, profitability can moderate the effect of dividend policy on debt policy, and profitability can moderate the effect of business risk on debt policy.